Application of Artificial Intelligence in Power System Monitoring and Fault Diagnosis - Wang, Guang; Xie, Jiale; Wang, Shunli (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Emerging technologies such as artificial intelligence (AI), big data analytics, and deep learning have received widespread attention in recent years and have shown great potential for application in many industrial fields. In power systems, AI and related technologies are also being used as new powerful tools that are gradually replacing the traditional techniques of feature modeling, performance control, and fault diagnosis, with better results. This reprint consists of 10 articles, all of which are authored by experts in the related fields, reporting the results of the latest research on the application of AI techniques in power systems, focusing on several novel and fascinating approaches to power system modeling and control, state estimation, performance diagnosis and prognosis.